2022
DOI: 10.3390/ijms231810438
|View full text |Cite
|
Sign up to set email alerts
|

AQP4, Astrogenesis, and Hydrocephalus: A New Neurological Perspective

Abstract: Aquaporin 4 (AQP4) is a cerebral glial marker that labels ependymal cells and astrocytes’ endfeet and is the main water channel responsible for the parenchymal fluid balance. However, in brain development, AQP4 is a marker of glial stem cells and plays a crucial role in the pathophysiology of pediatric hydrocephalus. Gliogenesis characterization has been hampered by a lack of biomarkers for precursor and intermediate stages and a deeper understanding of hydrocephalus etiology is needed. This manuscript is a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…The injections were performed in the right lateral ventricle following stereotactic coordinates (0.8 mm lateral, 1.7 mm anterior, and 1.5 mm deep from the posterior fontanelle) as previously described 21 . The solutions were administered over 30 seconds using a 25-microliter syringe (Hamilton, 80366) adapted to a UMP3 Ultra Micropump (World Precision Instruments) as previously reported 22,23 . The animals were anesthetized for hypothermia.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The injections were performed in the right lateral ventricle following stereotactic coordinates (0.8 mm lateral, 1.7 mm anterior, and 1.5 mm deep from the posterior fontanelle) as previously described 21 . The solutions were administered over 30 seconds using a 25-microliter syringe (Hamilton, 80366) adapted to a UMP3 Ultra Micropump (World Precision Instruments) as previously reported 22,23 . The animals were anesthetized for hypothermia.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…It is involved in brain edema caused by ischemia and other injuries, as well as in reactive astrocyte migration and glial scarring that occur after traumatic brain injury. AQP1, 3, 4, 5, 8, and 9 have been reported to be expressed to some extent in the brain [ 22 , 23 ], but the functions of AQP3 and 5 remain unclear. The co-expression of aquaporins in astrocytes results in cell swelling and then activates the transient receptor potential vanillin 4 (TRPV4) channels with a quick response to increased cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Castañeyra-Ruiz et al [ 7 ] revealed interesting data, proposing AQP4 as a possible biomarker for gliogenesis and ways in which alterations in AQP4 expression can be associated with pediatric hydrocephalus, with a specific emphasis on the repercussion of reactive astrogliosis in this pathological condition. According to Castañeira-Ruiz [ 7 ], unpolarized expression of AQP4 is found in proliferative cells with different morphologies in the human brain: in glial stem cells with long projections that are used for other cells to migrate and populate white matter tracks, and intermediate progenitor cells with an oval shape and lack of long projection. From these early stages of astrogenesis, AQP4 is expressed in polarized astrocyte endfeet, indicating the final stage of astrocyte maturation.…”
mentioning
confidence: 99%
“…These findings allow the authors to suggest the possible role of AQP4 in the early cell differentiation process during the first days of life in the newborn animal, which may be important for myelinization. Furthermore, as indicated by Castañeira-Ruiz et al in their review [ 7 ], in different animal models that end up developing congenital or perinatal hydrocephalus, changes in AQP4 expression cause premature differentiation of glial stem cells (GSC) into reactive astrocytes, causing neurodevelopmental disorders. This occurs because GSCs lose their projections toward the white matter tracks and glioblasts then lose their migration guidance for the correct formation of white matter, a typical finding observed in pediatric hydrocephalus.…”
mentioning
confidence: 99%
See 1 more Smart Citation